Antimicrobial Resistance and in silico Virulence Profiling of Aliarcobacter butzleri Strains From German Water Poultry - Müller, Eva; Hotzel, Helmut; Linde, Jörg; Hänel, Ingrid; Tomaso, Herbert (Frontiers in Microbiology, 2020)
Aliarcobacter butzleri is an emerging foodborne and zoonotic pathogen that is usually transmitted via contaminated food or water. A. butzleri is not only the most prevalent Aliarcobacter species, it is also closely related to thermophilic Campylobacter, which have shown increasing resistance in recent years. Therefore it is important to assess its resistance and virulence profiles. In this study, 45 Aliarcobacter butzleri strains from water poultry farms in Thuringia, Germany, were subjected to an antimicrobial susceptibility test using the gradient strip diffusion method and whole-genome sequencing. In the phylogenetic analysis, the genomes of the German strains showed high genetic diversity. Thirty-three isolates formed 11 subgroups containing two to six strains. The antimicrobial susceptibility testing showed that 32 strains were resistant to erythromycin, 26 to doxycycline, and 20 to tetracycline, respectively. Only two strains were resistant to ciprofloxacin, while 39 strains were resistant to streptomycin. The in silico prediction of the antimicrobial resistance profiles identified a large repertoire of potential resistance mechanisms. A strong correlation between a gyrA point mutation (Thr-85-Ile) and ciprofloxacin resistance was found in 11 strains. A partial correlation was observed between the presence of the bla3 gene and ampicillin resistance. In silico virulence profiling revealed a broad spectrum of putative virulence factors, including a complete lipid A cluster in all studied genomes.